Po Po Says : Eight Inspiring Stories in Asian American History - Ng, Ashley (United States : Goff Books, an Imprint of ORO Editions, 2022)
Did you know Filipino settlers were the first Asian American community? When Po Po knits, she shares parts of American history that are not often told. As her young granddaughter listens with admiration, Po Po talks about Asian Americans and how their resilience has helped shape the strength and beauty of the United States of America
Keywords: Asian Americans -- Juvenile literature; Children's stories, American; Picture books